La evaluación de desempeño, la percepción de justicia y las reacciones de los empleados - Fernández Palma, Marcos David (2009)
In this paper we consider the perceptions of justice and the employees’ reactions in relation to the process of performanceevaluation from a theoretical perspective.From the bibliographical review , we can conclude that the employees see justice in the performance evaluation whenthey observe certain conditions identified in the theory and they make possible a real validation of this procedure withthe following adoption of positive behaviours stated in the objectives of the organization.Nevertheless, it is possible to improve the different aspects of the performance process in every company and alsoimprove the justice perception as well as the level of reactions, because each of them is related to a type of justice.